Insulin Fused to Apolipoprotein A-I Reduces Body Weight and Steatosis in DB/DB Mice - Ardaiz, Nuria; Gomar, Celia; Vasquez, Marcos; Tenesaca, Shirley; Fernandez-Sendin, Myriam; Di Trani, Claudia Augusta; Belsué, Virginia; Escalada, Javier; Werner, Ulrich; Tennagels, Norbert; Berraondo, Pedro (Frontiers in Pharmacology, 2021)
BACKGROUND: Targeting long-lasting insulins to the liver may improve metabolic alterations that are not corrected with current insulin replacement therapies. However, insulin is only able to promote lipogenesis but not to block gluconeogenesis in the insulin-resistant liver, exacerbating liver steatosis associated with diabetes. METHODS: In order to overcome this limitation, we fused a single-chain insulin to apolipoprotein A-I, and we evaluated the pharmacokinetics and pharmacodynamics of this novel fusion protein in wild type mice and in db/db mice using both recombinant proteins and recombinant adenoassociated virus (AAV). RESULTS: Here, we report that the fusion protein between single-chain insulin and apolipoprotein A-I prolonged the insulin half-life in circulation, accumulated in the liver, and reduced lipogenic activity of the insulin. To validate this finding, we used AAV encoding insulin fused to apolipoprotein A-I or to albumin. We analyzed the long-term effect of these insulin analogs in the db/db mouse model of diabetes, obesity, and liver steatosis. While AAV encoding insulin fused to albumin exacerbated liver steatosis in several mice, AAV encoding insulin fused to apolipoprotein A-I reduced liver steatosis. These results were confirmed upon daily subcutaneous administration of the recombinant fusion protein for six weeks. The reduced liver steatosis was associated with reduced body weight in mice treated with insulin fused to apolipoprotein A-I. Recombinant apolipoprotein A-I alone significantly reduces body weight and liver weight, indicating that the apolipoprotein A-I moiety is the main driver of these effects. CONCLUSION: Thus, this fusion protein could be a promising insulin derivative for the treatment of diabetic patients with associated fatty liver disease.